A blockchain-based ITS framework with privacy preserving for secure and reliable communication. (23rd November 2021) - Panda, Soumyashree S.; Jena, Debasish; Mohanta, Bhabendu Kumar; Patnaik, Srikanta
With the omnipresence of technology, intelligent transportation system (ITS) is no more a distant dream but has become an achievable reality. One of the fundamental challenges in the implementation of an ITS is the proper management of security and privacy issues, especially how the system confirms the validity of its users. Most of the existing security mechanisms are based on a centralized framework and assume the registration authority and roadside units to be trustful. Therefore, a distributed framework using Blockchain and, a very lightweight and privacy-preserving authentication protocol employing an interactive zero-knowledge proof (ZKP) based on elliptic curve cryptography (ECC) is proposed. An in-depth analysis of the protocol demonstrates that it meets all the security and privacy requisites of an ITS. In addition, the suggested protocol is also validated using the widely used AVISPA tool. The reliability and effectiveness of the protocol are analyzed through simulation using NS2 which proves the practicality of the protocol.